Green Infrastructure Finance : Framework Report. - Baietti, Aldo (World Bank studies., 2012)
This report builds on the conclusions of the Green Infrastructure Finance: Leading Initiatives and Research report and lays out a simple and elegant way in which scarce public financing can leverage market interest in 'greening' infrastructure, particularly in the East Asia and Pacific Region. The framework introduced in the report bridges ideas and concepts between environmental economics and project finance practices and consists largely of an analytical methodology for determining the financial viability gap of low-emission projects and an approach for assessing and strengthening the green.